An MMTES algorithm for dynamic photovoltaic array reconfiguration to enhance power output under partial shading conditions. Issue 4 (20th January 2021) - Varma, G Harish Kumar; Barry, Venugopal Reddy; Jain, Rohit Kumar; Kumar, Devanand
Abstract: Partial shading is a severe impediment to the effective use of photovoltaic systems. It will lead to performance degradation in the photovoltaic system. This work proposes a maximum–minimum tier equalisation swapping reconfiguration algorithm for total‐cross‐tied connection under shading conditions. The proposed reconfiguration algorithm uses a switch matrix to alter the interconnection of modules in a photovoltaic array. The switch matrix dynamically modifies the connections based on the equalisation of tier irradiance. This algorithm applies to the symmetrical and asymmetrical photovoltaic array. Further, simulation studies show the efficacy of the proposed algorithm by minimising the multiple peaks and enhancing the output power compared with the traditional total‐cross‐tied configuration. The performance of experimental tests ascertains the feasibility of the proposed method.